Curvature of curve as an indicator of the optimal movement trajectory in physical rehabilitation. Elliptical rehabilitation movements - O. S. Vasilyev; S. P. Levushkin (National Electronic Information Consortium (NEICON), 2020)
The movement dynamic characteristics are the main parameters for physical exercise dosing during the athlete recovery process. However, taking into account the geometric characteristics of movement is no less important, especially when restoring the joint range of motion. The hypothesis of the study was the assumption that the use of movements' geometric characteristics allows to "design" the optimal physiological rehabilitation patterns for movement volume restoration. Objective: to develop general principles and to create a mathematical model of the optimal trajectory characteristics for the restored part of the athlete's musculoskeletal system. Materials and methods: We used 3D Qualisys Motion Capture and Analysis System in our investigation. The study involved 32 complex coordination sports athletes (age 9-15) with hip and ankle joint injuries (bruises, sprains strains). All they required a joint movement volume restoration. Results: The study revealed that joint movement volume restoration following the individually selected pathways involving effective mathematical modeling (study group) takes shorter time to restore the athletes than traditional physiotherapy methods (control group). For typical injuries (bruises, sprains and strains) of the hip joint area, the rehabilitation took 18±5 days for controls and 12±3 days for experimental group subjects. Nearly the same pattern was observed in restoration the ankle joint (12±4 days of recovery for controls versus 8±3 days for the experimental group). Conclusions: Restoring the joint movement volume, the workloads should be evaluated with geometric rather than dynamic indicators; for planar movement, that should be the distal limb path curvature relative to the restored joint.